Exosome-mediated delivery of RNA and DNA for gene therapy. (1st May 2021) - Munagala, Radha; Aqil, Farrukh; Jeyabalan, Jeyaprakash; Kandimalla, Raghuram; Wallen, Margaret; Tyagi, Neha; Wilcher, Sarah; Yan, Jun; Schultz, David J.; Spencer, Wendy; Gupta, Ramesh C.
Abstract: Gene therapy promises to revolutionize biomedicine and personalized medicine by modulating or compensating the expression of abnormal genes. The biggest obstacle for clinical application is the lack of an effective, non-immunogenic delivery system. We show that bovine colostrum exosomes and polyethyleneimine matrix (EPM) delivers short interfering RNA (siRNA) or plasmid DNA (pDNA) for effective gene therapy. KRAS, a therapeutic focus for many cancers, was targeted by EPM-delivered KRAS siRNA (si KRAS ) and inhibited lung tumor growth (>70%) and reduced KRAS expression (50%–80%). Aberrant p53 is another therapeutic focus for many cancers. EPM-mediated introduction of wild-type (WT) p53 pDNA ( pcDNA-p53 ) resulted in p53 expression in p53-null H1299 cells in culture, subcutaneous lung tumor, and tissues of p53-knockout mice. Additionally, chemo-sensitizing effects of paclitaxel were restored by exogenous WT p53 in lung cancer cells. Together, this novel EPM technology represents an effective 'platform' for delivery of therapeutic nucleic acids to treat human disease. Highlights: Exosomes and PEI matrix (EPM) represent a new exosomal-based nano delivery 'platform'. EPM is a biocompatible means for nucleic acid delivery. EPM provides high nucleic acid entrapment and protection from enzymatic degradation. EPM enhances the specificity of delivery by the addition of a targeting ligand. Intravenous dosing of EPM formulations was well tolerated with no adverse response.